PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PENDAFTARAN ONLINE PADA BPJS KESEHATAN MELALUI APLIKASI MOBILE JKN - Nova Indriani; Maiza Duana; Fitriani Fitriani; Yulizar Yulizar; Ihsan Murdani (PT.Mantaya Idea Batara, 2024)
Tremendous technical progress has defined the period of contemporary globalization. BPJS Kesehatan released a mobile application called JKN. The goal is thatcustomers can quickly benefit fromthe service.Theauthor conducted this study in order to understand and identifyhowto assess customer satisfactionand related service quality. BPJS Kesehatan online registrant via mobile JKN. The quantitative approach is the method taken in this study. Quantitative techniques are applied to deliberate data analysis after research instruments used for data collection challenge pre-existing assumptions. Based on research findings and data analysis, customer satisfaction of STNK JKN in South Aceh Regency is influenced by service quality. Based on the hypothesis test, it has shown that the calculated value (5.941>1.98472) or sig <? (0.00 = 0.00) is greater than the table inconclusion, client happiness is influenced by the quality of services provided, namely JKN car registration can be taken based on the findings of studies that have been conducted. This shows that customer satisfaction with JKN car registration is influenced by service quality variables, supporting the hypothesis. With an R2 of 0.284, it can be concluded that 28.4% of the satisfaction variable is explained by the service quality variable